Disability and cycling technology: A socio-historical analysis - Norcliffe, Glen; Buliung, Ron; Kruse, Annika; Radford, John (Disability Studies Quarterly, 2022)
This article explores longstanding links between cycling and disability. Social models of disability and closely related theories on the social construction of technology are central to our approach. The former insists that disability is a social construct; the latter views technology as socially formed. Disabled persons engage in cycling for, among other things, the pleasure of moving about the city and countryside, parks and neighbourhoods, to access places of work and study, and to gain greater independence in their daily lives. They have played an active role in the development and adaptation of cycles to make them better suited to particular needs. Disabled persons, their friends and family, and technicians have shared ideas and information to design cycling machines that reduce the limitations of technologies and environments developed for so-called "able" bodies. Here, we present a typology identifying seven types of cycles that were and are used by disabled persons for varying purposes. They are as follows: transporters, pedomotives, manumotives, sociables, stability machines, tandems, and power-assisted bikes. In each case, examples existed in the nineteenth century or earlier but social construction and improved materials and technology have dramatically enhanced their utility in recent years.